Analysis of loads and structural capacity of steel silo with corrugated wall for pelleted material - Antonowicz, Ryszard; Bywalski, Czesław; Kaminski, Mieczysław (Journal of Civil Engineering and Management, 2014)
This paper deals with problems connected with the design and operation of thin-walled steel silos for storing pelleted materials. A failure of a faultily designed silo is described and its causes are examined. The parameters of the stored material were determined. The exceptional (unforeseen) loads produced by arching and their consequences were analysed. In order to compare the effect of calculation assumptions on the degree of use of the load-bearing capacity of the stringer its buckling capacity under the stored material load alone was checked. On the basis of the analyses the probable course of the events leading to the failure was determined. It is pointed out that the exceptional loads and the disturbance of the bulk material flow by silo structural and technological fittings need to be taken into account in the design of silos.